Pengaruh celebrity endorser dan kepercayaan terhadap kepuasan konsumen dan dampaknya terhadap niat beli ulang - Azhari, Putri; Tjahjaningsih, Endang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The aim of this research is to examine the effect of celebrity endorsers and trust on consumer satisfaction, as well as their subsequent influence on repurchase intentions. The study was carried out on individuals who use Scarlett whitening products residing in the city of Jepara. The present study employed a non-probability sampling technique, specifically the method of distributing questionnaires randomly, with a predetermined sample size of 100 respondents. The present study employs primary data as its primary source of information. The findings of this research indicate that the utilization of celebrity endorsers has a noteworthy favorable impact on the level of customer satisfaction for Scarlett Whitening. Additionally, trust is observed to have a significant positive influence on customer satisfaction for Scarlett Whitening. Furthermore, the results suggest that customer satisfaction plays a crucial role in determining the repurchase intentions of Scarlett Whitening customers.